2021
DOI: 10.1002/adfm.202105992
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Nonvolatile Magnetization Switching and Multi‐Level States by Current in Single Van der Waals Topological Ferromagnet Fe3GeTe2

Abstract: Robust multi-level spin memory with the ability to write information electrically is a long-sought capability in spintronics, with great promise for applications. Here, nonvolatile and highly energy-efficient magnetization switching is achieved in a single-material device formed of van-der-Waals (vdW) topological ferromagnet Fe 3 GeTe 2 , whose magnetic information can be readily controlled by a tiny current. Furthermore, the switching current density and power dissipation are about 400 and 4000 times smaller … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 36 publications
0
38
0
Order By: Relevance
“…Next, on the basis of recent studies pertaining to current-controlled magnetism in FGT, we present a primary demonstration of nonlocal magnetism control via current. As shown in Figure , a long FGT strip with a thickness of 20 ± 1 nm was exfoliated and transferred onto a Si/SiO 2 substrate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, on the basis of recent studies pertaining to current-controlled magnetism in FGT, we present a primary demonstration of nonlocal magnetism control via current. As shown in Figure , a long FGT strip with a thickness of 20 ± 1 nm was exfoliated and transferred onto a Si/SiO 2 substrate.…”
Section: Resultsmentioning
confidence: 99%
“…A potential technique is to manipulate the magnetism of local sites nonlocally through in-plane magnetic interactions, which are closely related to the domains. For instance, a recent study pertaining to coercive field modulation in FGT demonstrated that currents can drive domain wall motion in FGT through spin–orbital torque (SOT) and Joule heating. ,− Therefore, the understanding of domain states and domain dynamics in 2D magnets is extremely important. For monolayer CrI 3 , domains can be observed directly via reflected magnetic circular dichroism (RMCD) and second-harmonic generation measurements .…”
mentioning
confidence: 99%
“…To first demonstrate imaging spintronic effects, we consider current-reduced coercivity, a phenomenon previously observed in FGT and reported to arise from bulk SOTs generated by the injection of currents directly in the FGT flake [9,10]. SOTs are supported in FGT by the broken inversion symmetry within its crystal structure [40,41].…”
Section: Observation Of Current-reduced Coercivitymentioning
confidence: 99%
“…S2(c)], clearly shows a spatial dependence of the strength of the magnetization which we attribute to areas of different thickness/number of layers. For instance, in the top part of the image the thick (thin) region of the flake with 23 (10) layers is found to have an average areal magnetization density of 50 µ B nm −2 (20 µ B nm −2 ). Assuming each iron ion contributes 1.5 µ B on average (as in bulk FGT at low temperatures [57]), we expect an areal magnetization density of 33 µ B nm −2 per monolayer.…”
Section: Reconstruction Of Magnetizationmentioning
confidence: 99%
See 1 more Smart Citation